Pengaruh Teknologi Keuangan Terhadap Inklusi Keuangan (Studi pada Penggunaan E-Wallet pada Mahasiswa S2 Univeristas Negeri Malang) - Wardanu, Aditya Putra; Fadhilah Nur Oktaviani; Shafa Annisa Puspasari; Ely Siswanto (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to analyze the effect of financial technology on financial inclusion among Masters Students at the State University of Malang. This study uses quantitative methods with descriptive and explanatory research types. The sampling technique uses non probability sampling and is carried out using purposive sampling. The sample in this research was Master's students at the UM who used e-wallets for financial transactions. The data collection technique uses a questionnaire. The data obtained was then analyzed using simple regression analysis techniques with using SPSS software. Keywords: E-Wallet, Financial Inclusion, Financial Technology.